Nonclinical Safety Profile of Etelcalcetide, a Novel Peptide Calcimimetic for the Treatment of Secondary Hyperparathyroidism. (May 2016) - Fielden, Mark R.; Dean, Charles; Black, Kurt; Sawant, Satin G.; Subramanian, Raju; Tomlinson, James E.; Walter, Sarah; Zimmermann, Cameron; Griggs, Mark W.; McKeon, Marie E.; Lewis, Elise M.; Beevers, Carol; et al.
Etelcalcetide is a noveld -amino acid peptide that functions as an allosteric activator of the calcium-sensing receptor and is being developed as an intravenous calcimimetic for the treatment of secondary hyperparathyroidism in patients with chronic kidney disease on hemodialysis. To support clinical development and marketing authorization, a comprehensive nonclinical safety package was generated. Primary adverse effects included hypocalcemia, tremoring, and convulsions. Other adverse effects were considered sequelae of stress associated with hypocalcemia. Cardiovascular safety evaluations in the dog revealed an anticipated prolongation of the corrected QT interval that was related to reductions in serum calcium. Etelcalcetide did not affect the human ether-a-go-go gene ion channel current. Etelcalcetide was mutagenic in some strains of Salmonella, however, based on the negative results in 2 in vitro and 2 in vivo mammalian genotoxicity assays, including a 28-day Muta mouse study, etelcalcetide is considered nongenotoxic. Further support for a lack of genotoxicity was provided due to the fact that etelcalcetide was not carcinogenic in a 6-month transgenic rasH2 mouse model or a 2-year study in rats. There were no effects on fertility, embryo–fetal development, and prenatal and postnatal development. All of the adverse effects observed in both rat and dog were considered directly or secondarily related to the pharmacologic activity of etelcalcetide and the expected sequelae associated with dose-related reductions in serum calcium due to suppression of parathyroid hormone secretion. These nonclinical data indicate no safety signal of concern for human risk beyond that associated with hypocalcemia and associated QT prolongation.